DETERMINATION OF ENVIRONMENTAL FACTORS AFFECTING DENGUE INCIDENCE IN SLEMAN DISTRICT, YOGYAKARTA, INDONESIA - Kesetyaningsih, Tri Wulandari; Andarini, Sri; Sudarto, Sudarto; Pramoedyo, Henny (African Journal of Infectious Diseases (AJID), 2018)
Background: Dengue is a disease related to the environment that spreads rapidly. Prevention movement is considered ineffective; therefore, a more efficient early warning system is required. It is required strongly correlated variables to as predictor in early warning system. This study aims to identify the environmental conditions associated with dengue.Materials and methods: This ecological study was conducted on five sub-districts selected based on the trend of the incidence. Data land cover and elevation obtained using GIS. Climate data were obtained from Meteorology and Climatology and Geophysics Agency of Yogyakarta.Results: There were 1.150 dengue cases from 2008-2013 obtained from District Health Office. The spatial pattern is clustered in all sub-districts (Z-score < -2.58). There is a positive correlation between land cover and dengue (p 0.000; r 0.284) and a negative correlation between elevation areas and dengue (p 0.000; r - 0.127). Multiple Regression Test shows the effect of humidity (p 0.000) and rainfall (p 0.002) with a contribution of 13.5% - 27.4% (r2 0.135 – 0.274), while temperature has no effect in all sub-districts (p > 0.05). There is no effect of climate parameters in sporadic dengue areas (p > 0.05).Conclusion: It is concluded that dengue in Sleman is clustered and associated with the environment parameter, even though it does not have close correlation. High elevated and small building area is consistent with the lower dengue cases. Humidity and rainfall affect dengue, but temperature does not affect dengue.